Lived experiences of women with type 2 diabetes in Uzbekistan: A descriptive phenomenological study - Yuldashev, Dilshodbek; Karimova, Nargiza; Nursultanov, Aidos; Zhanabekova, Aigerim (STIKes Al-Ma'arif Baturaja, 2025)
Background Type 2 diabetes mellitus (T2DM) presents significant challenges beyond glycemic control, particularly for women in culturally conservative societies. In Uzbekistan, women with diabetes often face psychological burdens, social stigma, and role conflict, yet little is known about their lived experiences. Objective This study aimed to explore the lived experiences of women with type 2 diabetes in Uzbekistan and to understand how they interpret and cope with the condition within their cultural and social environments. Methods A qualitative descriptive phenomenological approach was used. Sixteen women diagnosed with T2DM for at least one year were recruited purposively from outpatient clinics in Tashkent and Samarkand. Data were collected through semi-structured in-depth interviews and analyzed using Colaizzi’s method. Lincoln and Guba’s trustworthiness criteria guided the rigor of the study. Results Four major themes emerged: (1) altered perception of life with diabetes, (2) psychosocial challenges and emotional burden, (3) coping strategies and spiritual resilience, and (4) disruption of family roles and responsibilities. Participants described diabetes as a constant and invisible burden, exacerbated by stigma, misunderstanding, and gendered expectations. Despite these challenges, many women relied on spirituality and structured routines to regain control and meaning. Conclusion Women with T2DM in Uzbekistan experience diabetes as a complex emotional and social phenomenon. Addressing their needs requires culturally sensitive interventions that integrate psychosocial support, family involvement, and gender-responsive health education.